2023
DOI: 10.1021/acsomega.3c07246
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Pd-to-Ag Ratio to Enhance the Synergistic Activity of Fly Ash-Supported PdxAgy Bimetallic Nanoparticles

Niladri Maity,
Aman Mishra,
Samir Barman
et al.

Abstract: Fly ash (FA)-supported bimetallic nanoparticles (Pd x Ag y /FA) with varying Pd:Ag ratios were prepared by coprecipitation of Pd and Ag involving in situ reduction of Pd­(II) and Ag­(I) salts in aqueous medium. All the supported nanoparticles were thoroughly characterized with the aid of powder X-ray diffraction (PXRD), X-ray photoelectron spectroscopy (XPS), electron microscopy (field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM)), and elemental analyses, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…In the above two studies, we found that in hydrogen gas evolution and in the photocatalytic degradation study of IBU, CuCo(3:1) ratio came out to be the best catalyst out of the other two ratios, i.e., CuCo(1:1) and CuCo(1:3). This is because, for attaining an optimum synergistic effect in bimetallic catalysts, tuning of the two-metal ratio is a very important factor for achieving better photocatalytic property …”
Section: Results and Discussionmentioning
confidence: 99%
“…In the above two studies, we found that in hydrogen gas evolution and in the photocatalytic degradation study of IBU, CuCo(3:1) ratio came out to be the best catalyst out of the other two ratios, i.e., CuCo(1:1) and CuCo(1:3). This is because, for attaining an optimum synergistic effect in bimetallic catalysts, tuning of the two-metal ratio is a very important factor for achieving better photocatalytic property …”
Section: Results and Discussionmentioning
confidence: 99%
“…[46,47] The absence of extraneous reflexes on the X-ray indicates the presence of high purity sillimanite, which is rare and makes such a cenosphere a valuable demanded raw material. [48,49,50] Minerals of the sillimanite group are quite common, have a relatively high hardness (6-7 points on the Mohs scale), do not dissolve in acids, which is why they are actively used in the metallurgy, ceramics, insulating and chemically resistant materials production, also high purity sillimanite is a raw material for the production of mullite and mullite refractory materials. [51,52] Resulting catalyst was investigated with SEM-microscopy.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%